Diversity arborial and vegetation indices in environment school - Callejas, Ivan Julio Apolonio; Durante, Luciane Cleonice; Oliveira, Angela Santana de; Noqueira, Marta Cristina de Jesus Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Studies have shown the importance of tree diversity in terms of environmental education and for ethical behavior of the students in environmental school. However, there are few studies with a standard proposed method for determining the arboreal vegetation existing inside the schools environmental. There is also a lack of index trees that can be used to design areas for vegetation inside these environments. This study aimed to conduct an environmental assessment in three schools located the Cuiabá city. It was carried out an arboreal inventory and vegetation indexes, in order to evaluate indexes that can be used as references for designing landscape projects for educational environments, as well as to be used in planning, conservation and maintenance of arboreal vegetation existing in these spaces. It was noted in school environment investigated that there was equilibrium between the native and exotic species and it was observed high relative frequency of two species. The largest values of leaf area index was determined in exotic trees such as Manguifera Indica L. and Ficus benjamina, as well as in the native one, like Licania tomentosa (Oiti). The results suggest shading arborization index equal or greater than 40% and school arboreal vegetation index at least equal to 12m2 per student for educational environments.